2016
DOI: 10.1002/pen.24274
|View full text |Cite
|
Sign up to set email alerts
|

A review on electrospun polymer nanostructures as advanced bioactive platforms

Abstract: This review article deals with latest literature studies on the potential use of polymer ultrathin and nanosized structures obtained by electrospinning to design novel engineered materials with bioactive properties. The electrofluidodynamic process offers the option to form high-performance bioactive systems based on polymer yarns of nanofibers or coatings of nanobeads with high surface-to-volume ratios. The electrospun and electrosprayed nanostructures can be further functionalized by encapsulation with bioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 367 publications
(418 reference statements)
0
92
0
1
Order By: Relevance
“…Recent advances in this field have shown that multilayer systems containing electrospun ultrathin fibers, that is, both submicron fibers and nanofibers, can significantly contribute to improve the barrier performance of biopolymers . Additionally, more remarkably, the electrospinning technology provides novel routes to develop novel active and bioactive functionalities, for instance packaging materials with antimicrobial performance and control release capacity of health‐promoting functional ingredients …”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in this field have shown that multilayer systems containing electrospun ultrathin fibers, that is, both submicron fibers and nanofibers, can significantly contribute to improve the barrier performance of biopolymers . Additionally, more remarkably, the electrospinning technology provides novel routes to develop novel active and bioactive functionalities, for instance packaging materials with antimicrobial performance and control release capacity of health‐promoting functional ingredients …”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning is a simple and versatile technique for fabricating nanofibers and fibrous mats, capable of producing continuous nanofibers with various types of surface morphology . Because of its numerous advantages, the procedure has been widely employed with variety of polymers in various applications . Although the single‐step electrospinning and electrospray processes have developed rapidly in creating different kinds of micro‐/nano structures such as core–shell and Janus, how to manipulate the behaviors of working fluid under electrical fields for high‐throughput production is still a big concern .…”
Section: Introductionmentioning
confidence: 99%
“…Both electrospinning and electrospraying can be used as a reliable approach for nanoencapsulation of active and bioactive components with high surface to volume ratio, porosity, and versatility. Importantly, research has proven the suitability of EHDP for packaging applications (Echegoyen et al., 2017; Torres‐Giner, Pérez‐Masiá, & Lagaron, 2016).…”
Section: Multilayer Film Preparation Techniquesmentioning
confidence: 99%